Birds optimize fruit size consumed near their geographic range limits - Martins, Lucas P.; Stouffer, Daniel B.; Blendinger, Pedro G.; Böhning-Gaese, Katrin; Costa, José Miguel; Dehling, D Matthias; Donatti, Camila I.; Emer, Carine [UNESP]; Galetti, Mauro [UNESP]; Heleno, Ruben; Menezes, Ícaro; Morante-Filho, José Carlos; et al. (American Association for the Advancement of Science (AAAS), 2024)
Animals can adjust their diet to maximize energy or nutritional intake. For example, birds often target fruits that match their beak size because those fruits can be consumed more efficiently. We hypothesized that pressure to optimize diet-measured as matching between fruit and beak size-increases under stressful environments, such as those that determine species' range edges. Using fruit-consumption and trait information for 97 frugivorous bird and 831 plant species across six continents, we demonstrate that birds feed more frequently on closely size-matched fruits near their geographic range limits. This pattern was particularly strong for highly frugivorous birds, whereas opportunistic frugivores showed no such tendency. These findings highlight how frugivore interactions might respond to stressful conditions and reveal that trait matching may not predict resource use consistently.